Effects of differential rates of alternative reinforcement on resurgence of human behavior. Issue 1 (January 2017) - Smith, Brooke M.; Smith, Gregory S.; Shahan, Timothy A.; Madden, Gregory J.; Twohig, Michael P.
Abstract : Despite the success of exposure‐based psychotherapies in anxiety treatment, relapse remains problematic. Resurgence, the return of previously eliminated behavior following the elimination of an alternative source of reinforcement, is a promising model of operant relapse. Nonhuman resurgence research has shown that higher rates of alternative reinforcement result in faster, more comprehensive suppression of target behavior, but also in greater resurgence when alternative reinforcement is eliminated. This study investigated rich and lean rates of alternative reinforcement on response suppression and resurgence in typically developing humans. In Phase 1, three groups (Rich, n = 18; Lean, n = 18; Control, n = 10) acquired the target response. In Phase 2, target responding was extinguished and alternative reinforcement delivered on RI 1 s, RI 3 s, and extinction schedules, respectively. Resurgence was assessed during Phase 3 under extinction conditions for all groups. Target responding was suppressed most thoroughly in Rich and partially in Lean. Target responding resurged in the Rich and Lean groups, but not in the Control group. Between groups, resurgence was more pronounced in the Rich group than the Lean and Control groups. Clinical implications of these findings, including care on the part of clinicians when identifying alternative sources of reinforcement, are discussed.